The rocket interferometer tracking (RIT) system - Spafford, Michael (1965)
A Rocket Interferometer Tracking (RIT) system is described. It uses a modified 108 Me Minitrack receiver converted for 73.6 Me operation and a newly developed phase measuring system. The output of the system is real time direction cosine data for two channels, East-West and North-South, in analog and digital form. The analog data are recorded on an x-y recorder and on a strip chart recorder; and the digital data are automatically recorded on punched tape. The RIT system has been integrated with the ranging portion of the Radio Doppler Interferometer Tracking system (RADINT) at the Wallops Island Launch facility, and records the range data on the same punched tape.